Biosynthesis of Chuangxinmycin Featuring a Deubiquitinase‐like Sulfurtransferase. Issue 46 (7th October 2021) - Zhang, Xingwang; Xu, Xiaokun; You, Cai; Yang, Chaofan; Guo, Jiawei; Sang, Moli; Geng, Ce; Cheng, Fangyuan; Du, Lei; Shen, Yuemao; Wang, Sheng; Lan, Haidong; et al.
Abstract: The knowledge on sulfur incorporation mechanism involved in sulfur‐containing molecule biosynthesis remains limited. Chuangxinmycin is a sulfur‐containing antibiotic with a unique thiopyrano[4, 3, 2‐ cd ]indole (TPI) skeleton and selective inhibitory activity against bacterial tryptophanyl‐tRNA synthetase. Despite the previously reported biosynthetic gene clusters and the recent functional characterization of a P450 enzyme responsible for C−S bond formation, the enzymatic mechanism for sulfur incorporation remains unknown. Here, we resolve this central biosynthetic problem by in vitro biochemical characterization of the key enzymes and reconstitute the TPI skeleton in a one‐pot enzymatic reaction. We reveal that the JAMM/MPN + protein Cxm3 functions as a deubiquitinase‐like sulfurtransferase to catalyze a non‐classical sulfur‐transfer reaction by interacting with the ubiquitin‐like sulfur carrier protein Cxm4GG. This finding adds a new mechanism for sulfurtransferase in nature. Abstract : Biochemical basis of the sulfur‐incorporation reaction during chuangxinmycin biosynthesis is elucidated. Particularly, the deubiquitinase‐like Cxm3 stands for the first JAMM/MPN + family protein catalyzing a sulfur‐transfer reaction, instead of the typical amido‐bond hydrolysis reaction, by interacting with a ubiquitin‐like sulfur carrier protein Cxm4GG.